2011
DOI: 10.1021/jf104246z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Sterol Composition of 10 Types of Mushrooms from Retail Suppliers in the United States

Abstract: Vitamin D(2) (ergocalciferol) and sterols were analyzed in mushrooms sampled nationwide in the United States to update the USDA Nutrient Database for Standard Reference. Vitamin D(2) was assayed using HPLC with [(3)H]-vitamin D(3) internal standard and sterols by GC-FID mass spectrometric (MS) confirmation. Vitamin D(2) was low (0.1-0.3 μg/100 g) in Agaricus bisporus (white button, crimini, portabella) and enoki, moderate in shiitake and oyster (0.4-0.7 μg/100 g), and high in morel, chanterelle, maitake (5.2-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
5
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 42 publications
8
139
5
5
Order By: Relevance
“…Strain Kanmycel 3-1 contained the highest content of ergosterol in comparison with other white A. bisporus, while Sylvan A15 contained the lowest content of ergosterol among all analyzed species. The findings clearly indicate lower levels of ergosterol in comparison to other studies showing that ergosterol content in A. bisporus ranged from 4.6 to 6.4 mg/g DW (460-640 mg/100 g DW) [15,51] and more than 50 mg/100 g fresh weight [45]. However, the obtained results are in accordance with other studies that have found that the total ergosterol content in brown A. bisporus was significantly higher than in white A. bisporus [45,50,51].…”
Section: Organic Acid Profilecontrasting
confidence: 51%
See 2 more Smart Citations
“…Strain Kanmycel 3-1 contained the highest content of ergosterol in comparison with other white A. bisporus, while Sylvan A15 contained the lowest content of ergosterol among all analyzed species. The findings clearly indicate lower levels of ergosterol in comparison to other studies showing that ergosterol content in A. bisporus ranged from 4.6 to 6.4 mg/g DW (460-640 mg/100 g DW) [15,51] and more than 50 mg/100 g fresh weight [45]. However, the obtained results are in accordance with other studies that have found that the total ergosterol content in brown A. bisporus was significantly higher than in white A. bisporus [45,50,51].…”
Section: Organic Acid Profilecontrasting
confidence: 51%
“…The findings clearly indicate lower levels of ergosterol in comparison to other studies showing that ergosterol content in A. bisporus ranged from 4.6 to 6.4 mg/g DW (460-640 mg/100 g DW) [15,51] and more than 50 mg/100 g fresh weight [45]. However, the obtained results are in accordance with other studies that have found that the total ergosterol content in brown A. bisporus was significantly higher than in white A. bisporus [45,50,51]. The concentration of ergosterol was confirmed to be different depending on the type of fungus [15,51].…”
Section: Organic Acid Profilecontrasting
confidence: 51%
See 1 more Smart Citation
“…Ergosterol is a precussor of vitamin D found in mushrooms membrane and known to vary among species depending on the physiological state of the mushroom (Chiocchio & Matković, 2011). Steroids in general have been reported to play several biological functions such as anti-tumor, anti-oxidant, immune function as well as prevention of common diseases (Phillips et al, 2011). Antrodia camphorata is a medicinal mushroom with reported anti-inflammatory activity (Hseu et al, 2005;Liu et al, 2007;Hsieh et al, 2010;Hseu, Huang, & Hsiang, 2010;Lee et al, 2011b;Liao, Kuo, Liang, Shen, & Wu, 2012;Deng et al, 2013;Chen et al, 2013).…”
Section: Steroidsmentioning
confidence: 99%
“…Nevertheless, ergosterol is also found in relatively high amounts in plants like corn, cotton seed, peanut and linseed oils (Kritchevsky and Shirley 2005;Lagarda et al 2006). This sterol is becoming an important research topic because its content is usually associated with structural and growing fungal characteristics, such as maturation, hyphal formation and sporulation (Villares et al 2012), being also dependent on the fungal species (Phillips et al 2011). From the bioactivity point of view, ergosterol has great importance since it can be converted into vitamin D 2 after photolysis and thermal rearrangement (Villares et al 2012), and was reported as having health-promoting properties such as antioxidant (Shao et al 2010), anti-inflammatory (Kuo et al 2011) and antihyperlipidemic (Hu et al 2006) activities, being also involved in the activated expression of specific defense genes (Lochman and Mikes 2005).…”
Section: Introductionmentioning
confidence: 99%